Analysis of Directive Speech Acts in Mata Najwa Youtube Channel Because of Corona: Why Indonesia Is Not Like Singapore - Anindya Prawita; Asep Purwo Yudi Utomo (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2020)
The translation of a speech often requires for attention. That's because in speech, speakers may have another purpose. Another purpose in the speech could be get the speech partner to do something. In that case, it is referred to as a directive speech. The purpose of this research is to describe directive speech that is found in Mata Najwa's youtube channel entitled